A design of 2.4 giga hertz to 5 giga hertz microstrip bandstop filter / Azizah Rosleh Fung - Rosleh Fung, Azizah
A design of a microstrip bandstop filter (BSF) is presented in this paper. The filter is designed to give a bandwidth of 70 percent, centered at 3.7 GHz with lower and upper cut-off frequency of 2.4 GHz and 5 GHz respectively. The filter is required to have an insertion loss of at least 60 dB with passband ripple of 0.1 dB. The design involves a Tschebychev third order bandstop filter whose input to output is matched to 50 Q impedance. The bandstop filter was realized to an open-circuited transmission lines and spaced by unit elements (UE)s which a quarter-wave long at mid-stop-band frequency. The proposed bandstop filter was simulated by using Genesys CAD package and fabricated on a microstrip that have relative permittivity of 2.33, and substrate and copper thickness of 0.5 mm and 0.0356 mm respectively. The filter is then measured using a Scalar Network Analyzer and lastly a data analysis is done to compare both result from simulation and measurement.